STRATEGI MEMPERTAHANKAN LOYALITAS PELANGGAN PADA USAHA KULINER DI KECAMATAN BENGKAYANG - Friska; Sabinus (Inovasi Pembangunan : Jurnal Kelitbangan, 2023)
This study aims to determine the strategy to maintain customer loyalty in the culinary business. This research was conducted in the Bengkayang sub-district from November 2022-June 2023. Based on the results of the research, food is a basic need that humans really need every day. All materials that are processed or not processed and eaten by humans will be beneficial to the body. Along with the development of the era, facts about culinary have also developed rapidly. Not a few people choose to open a business in the culinary field. This is because a unique food or drink is easily recognized by many people. There are also many entrepreneurs who work in the culinary field not only because they want to get profit and income, but also want to develop existing talents so that they become more useful for themselves and others. Culinary entrepreneurs in Bengkayang District carry out several strategies to retain their customers, namely by maintaining product quality, service quality, consumer satisfaction and carrying out additional strategies using the 4P marketing mix